2012
DOI: 10.1111/j.1365-2826.2011.02275.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Levothyroxine Treatment on Maternal Subclinical Hypothyroidism Improves Spatial Learning of Offspring in Rats

Abstract: Maternal hypothyroidism has adverse effects on neural development in the offspring. The present study aimed to investigate whether maternal subclinical hypothyroidism impairs spatial learning in the offspring, as well as the efficacy and optimal time of levothyroxine (L-T(4)) treatment in pregnancy. Female adult Wistar rats were randomly divided into six groups (n = 10 per group): control, hypothyroid (H), subclinical hypothyroid (SCH) and SCH treated with L-T(4), starting from the tenth, thirteenth and sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 37 publications
3
36
1
1
Order By: Relevance
“…Previous reports have documented that maternal thyroid dysfunction could affect the expression of BDNF and cause neurological defects in neonates [40] and adult rats [11]. Our previous studies [10,41] reported that maternal subclinical hypothyroidism decreased BDNF expression in rat pup hippocampi and impaired spatial learning; pups required more time during the Morris water maze test to find the hidden platform, compared with pups from NI mothers. The present study found that BDNF protein levels were decreased in the hippocampi of the pups from both the 3HI and LI mothers.…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports have documented that maternal thyroid dysfunction could affect the expression of BDNF and cause neurological defects in neonates [40] and adult rats [11]. Our previous studies [10,41] reported that maternal subclinical hypothyroidism decreased BDNF expression in rat pup hippocampi and impaired spatial learning; pups required more time during the Morris water maze test to find the hidden platform, compared with pups from NI mothers. The present study found that BDNF protein levels were decreased in the hippocampi of the pups from both the 3HI and LI mothers.…”
Section: Discussionmentioning
confidence: 92%
“…Currently the benefits of treatment with levothyroxine for women with hypothyroidism during pregnancy remain controversial. The results of meta-analysis of randomized control trials revealed that Levothyroxine (LT4) therapy significantly reduced the miscarriage rate, gestational diabetes, and gestational hypertension, but not preeclampsia [25]. Moreover, the study found that LT4 group had fewer preterm deliveries, birth weights <2500 g, deaths, and congenital malformations compared to control group in regards to neonatal outcomes [25].…”
Section: Discussionmentioning
confidence: 99%
“…The results of meta-analysis of randomized control trials revealed that Levothyroxine (LT4) therapy significantly reduced the miscarriage rate, gestational diabetes, and gestational hypertension, but not preeclampsia [25]. Moreover, the study found that LT4 group had fewer preterm deliveries, birth weights <2500 g, deaths, and congenital malformations compared to control group in regards to neonatal outcomes [25]. A recent study showed that LT4 therapy is associated with a reduced risk of low birth weight (LBW) offspring and a low Apgar score among women with subclinical hypothyroidism [26].…”
Section: Discussionmentioning
confidence: 99%
“…These doses were chosen based on a recent report that mice exposed to 10 mg/kg TCS exhibited urinary TCS levels equivalent to those of spontaneous abortion patients5. Levothyroxine (T4) (Sigma-Aldrich Inc., St. Louis, MO, USA) was dissolved in 0.9% saline solution and injected (20 μg/kg/day) subcutaneously (s.c.)44. The mTOR inhibitor rapamycin (Sigma-Aldrich Inc., St Louis, MO, USA) and the PI3K inhibitor LY294002 (Sigma-Aldrich Inc., St. Louis, MO, USA) were dissolved in 0.9% saline solution.…”
Section: Methodsmentioning
confidence: 99%